1972
DOI: 10.1073/pnas.69.6.1421
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Influenza Virus Replication by α-Amanitin: Mode of Action

Abstract: The replication of influenza virus in chick embryo fibroblast cells is inhibited by a-amanitin added during the first 2 hr of infection at concentrations similar to those required to inhibit cellular DNA-dependent RNA polymerase form II in vivo. Of two periods of increased RNA synthesis observed in cells infected with influenza virus, only the first, occurring from 0 to 2 hr after infection, is sensitive to a-amanitin. During this early period, there is a stimulation of the activity of DNA-dependent RNA polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 28 publications
2
30
1
Order By: Relevance
“…2). A similar dependence was previously reported for members of the family Orthomyxoviridae (15,28), which use the cap structure of cellular mRNAs as primers for their own transcription (3,14). It remains unknown whether NYMV might use a similar mechanism to cap its transcripts or whether RNA polymerase II activity is required for a different step in the NYMV replication cycle.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…2). A similar dependence was previously reported for members of the family Orthomyxoviridae (15,28), which use the cap structure of cellular mRNAs as primers for their own transcription (3,14). It remains unknown whether NYMV might use a similar mechanism to cap its transcripts or whether RNA polymerase II activity is required for a different step in the NYMV replication cycle.…”
Section: Discussionmentioning
confidence: 65%
“…Taken together, these results demonstrated that replication of the NYMV genome includes the nucleus. We next asked whether NYMV multiplication may be dependent on the activity of cellular RNA polymerase II as in the case of other RNA viruses that replicate in the nucleus such as influenza A virus and Thogoto virus (15,28). To check this, we infected Vero cells with NYMV in the presence of either plain medium or medium containing 5 g/ml of actinomycin D to block the activity of RNA polymerase II.…”
Section: Resultsmentioning
confidence: 99%
“…However, the structures of in vivo and in vitro synthesized mRNA do differ in that the in vitro mRNAs are shorter and lack a 5' methylated cap structure (Hay et al, 1977. Furthermore, primary transcription in vivo is sensitive to the drugs actinomycin D and alpha-amanitin (inhibitors of host cell DNA-dependent RNA polymerase ll), whereas transcription in vitro is insensitive to these drugs (Scholtissek & Rott, 1970;Penhoet et aL, 1971;Mahy et aL, 1972;Lamb & Choppin, 1977;Spooner & Barry, 1977). In addition, the influenza virion transcriptase was shown to possess another unusual property in that a number of guanosine related compounds, particularly the dinucleoside adenyl (3' to 5') guanosine (ApG), stimulate RNA synthesis in vitro by acting as primers for RNA synthesis (McGeoch & Kitron, 1975;Plotch & Krug, 1977).…”
mentioning
confidence: 99%
“…These results strongly support our earlier hypothesis (2,3) that viral RNA transcription in vio requires priming by RNAs synthesized by the host cell nuclear RNA polymerase II-i.e., by host mRNAs or their precursors. The need for continued synthesis of these primer host mRNAs provides an explanation for the inhibition of in vivo viral RNA transcription by a-amanitin (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%